1998
DOI: 10.1143/jjap.37.6628
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sub-Target in the Transversely Excited Atmospheric Pressure CO 2 Laser-Induced Shock-Wave Plasma

Abstract: A transversely excited atmospheric pressure (TEA) CO2 laser pulse (50 mJ, 100 ns) was focused on silicon grease which is painted on a copper plate as a subtarget with a power density of 6 GW/cm2 under reduced pressure. The comparison of the characteristics of the induced laser plasma between two cases, with subtarget and without subtarget was made. It is proved that the emission spectrum assigned to the silicon atom can be detected only for the case with the subtarget. It is also proved that in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In this experiment, a brass plate was placed on the backside of the sample in a close contact as a sub-target to enhance the ablation speed. In our previous works, for TEA CO 2 laser bombardment, it was proved that for soft samples, the use of a metal sub-target was essential to overcome the low ablation speed due to the lack of repulsive force [18,[31][32][33]. In fact, in this experiment, fluorine emission cannot be detected when the sub-target was not used even though a crater actually formed on the sample surface.…”
Section: Resultsmentioning
confidence: 92%
“…In this experiment, a brass plate was placed on the backside of the sample in a close contact as a sub-target to enhance the ablation speed. In our previous works, for TEA CO 2 laser bombardment, it was proved that for soft samples, the use of a metal sub-target was essential to overcome the low ablation speed due to the lack of repulsive force [18,[31][32][33]. In fact, in this experiment, fluorine emission cannot be detected when the sub-target was not used even though a crater actually formed on the sample surface.…”
Section: Resultsmentioning
confidence: 92%
“…In the case of LiFePO 4 sheet, three typical Li emission lines were detected more clearly than those of LiFePO 4 pellet (figure 3). In order to clarify this result, we assume that the atomization process in a thin film sample was easier to proceed than that in the hard bulk or pellet sample [14]. The effect of the sub-target may also occur in this case of LiFePO 4 pellet.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, LISPS cannot be applied directly to liquid or soft solid samples. [21][22][23] In order to overcome the above problem, we introduced a new technique in which the liquid samples was immediately freezed using a mixture of dry ice and alcohol. It should be noted that the freezing process should be done fast to get a homogeneity in the form of ice sample.…”
Section: Resultsmentioning
confidence: 99%
“…We have nevertheless proved that even for soft sample, shockwave plasma was readily produced when a hard subtarget was placed behind them. [21][22] In order to improve our LISPS technique to liquid sample, recently we have succeeded in applying the laser-induced shockwave plasma spectroscopy (LISPS) for the detection and analysis of metal elements deposited from water sample by means of electrolysis method. It is shown that the elements are generally deposited in the form of thin film on the electrode surface, while the electrode also conveniently serves as a subtarget for the relatively soft metal film, and thereby provides the necessary condition for the generation of shockwave plasma which is favorable for highly sensitive spectrochemical analysis.…”
Section: Introductionmentioning
confidence: 99%